Predicting the biological behavior of non-muscle-invasive bladder cancer: from histology to molecular taxonomy - Luchini, Claudio; Cheng, Liang (Translational Andrology and Urology; Vol 6, No 5 (October 26, 2017): Translational Andrology and Urology (Management of Penile Cancer), 2017)
Urinary bladder cancer represents the seventh most common cancer worldwide; the most common type of bladder cancer is urothelial carcinoma (1). About 75% of patients are initially diagnosed with non-muscle-invasive bladder cancer (NMIBC), whose treatment includes a surveillance regimen based on risk stratification for recurrence and progression (1,2). The need for intensive and long-term follow-up, mainly represented by cystoscopic examinations with biopsies, makes bladder cancer the most expensive cancer to treat (3).